Peran Kepuasan Pengguna Dalam Mendorong Niat Menggunakan Ulang pada Pengguna Tiket.com - Wijayanti, Farah Nur Syafi’ah; Regita Septiani Putri (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
Indonesia is the largest consumer of K-pop music globally. The high number of K-pop music consumers has triggered the widespread phenomenon of "Ticket War" among fans, resulting in increased traffic loads on tiket.com as one of the platforms for purchasing concert tickets. This study aims to analyze the effect of system quality and service quality on reuse intention, with user satisfaction as a mediating variable. This research used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 300 respondents who had participated in K-pop concert ticket wars using the tiket.com application. The sampling technique used was purposive sampling, and data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3. The results indicate that system quality and service quality positively and significantly affect user satisfaction and reuse intention. User satisfaction also has a positive and significant effect on reuse intention and mediates the relationship between system quality and service quality with reuse intention. This study provides insights for tiket.com management to improve service quality and user satisfaction.